SHARIA ANALYSIS AND FINANCIAL MANAGEMENT OF QORDUL HASAN IN LAZIZMA PRODUCTS - Hosnan, Hosnan; Huda, Ach. Robertul; Ramin, Moh. (Ngejha, 2023)
This study aims to analyze the understanding and implementation of the Qordul Hasan contract on Lazizma products at KSPPS BMT NU Ketapang Branch, as well as evaluate aspects of sharia and financial management to improve compliance with sharia principles. This research method uses a qualitative approach with a case study at the KSPPS BMT NU Ketapang Branch. Data was collected through in-depth interviews with managers, staff, and customers involved in Lazizma's products, as well as document analysis related to policies and procedures for the implementation of the Qordul Hasan contract. The data analysis technique was carried out descriptively to identify the level of understanding of the Qordul Hasan contract, evaluate the implementation from a Sharia perspective, and assess the effectiveness of financial management in maintaining compliance. The results of the study show that the understanding of the Qordul Hasan contract at KSPPS BMT NU Ketapang Branch is generally good, with implementation following sharia principles. This contract provides benefits in the form of interest-free loans that ease the burden on customers. However, there are several challenges in its implementation, including the need to increase education about this contract and improve managerial procedures to make it more efficient. This research provides important insights on how the understanding and implementation of the Qordul Hasan contract can be improved to improve sharia compliance in Islamic financial institutions. This finding is expected to help KSPPS BMT NU Ketapang Branch in optimizing the implementation of the Qordul Hasan contract and increasing customer satisfaction and compliance.